Human information retrieval - Warner, Julian, 1955- (MIT Press, 2010)
Julian Warner offers a comprehensive overview of information retrieval, synthesizing theories from different disciplines and incorporating such disparate systems as WorldCat and Google into a single, robust theoretical framework.
Keywords: Information retrieval.; elektronické knihy; electronic books